Non-cell autonomous cues for enhanced functionality of human embryonic stem cell-derived cardiomyocytes via maturation of sarcolemmal and mitochondrial K(ATP) channels - Keung, Wendy (Sci Rep, 2016)
Human embryonic stem cells (hESCs) is a potential unlimited ex vivo source of ventricular (V) cardiomyocytes (CMs), but hESC-VCMs and their engineered tissues display immature traits. In adult VCMs, sarcolemmal (sarc) and mitochondrial (mito) ATP-sensitive potassium (K(ATP)) channels play crucial roles in excitability and cardioprotection. In this study, we aim to investigate the biological roles and use of sarcK(ATP) and mitoK(ATP) in hESC-VCM. We showed that SarcI(K, ATP) in single hESC-VCMs was dormant under baseline conditions, but became markedly activated by cyanide (CN) or the known opener P1075 with a current density that was ~8-fold smaller than adult; These effects were reversible upon washout or the addition of GLI or HMR1098. Interestingly, sarcI(K, ATP) displayed a ~3-fold increase after treatment with hypoxia (5% O(2)). MitoI(K, ATP) was absent in hESC-VCMs. However, the thyroid hormone T3 up-regulated mitoI(K, ATP,) conferring diazoxide protective effect on T3-treated hESC-VCMs. When assessed using a multi-cellular engineered 3D ventricular cardiac micro-tissue (hvCMT) system, T3 substantially enhanced the developed tension by 3-folds. Diazoxide also attenuated the decrease in contractility induced by simulated ischemia (1% O(2)). We conclude that hypoxia and T3 enhance the functionality of hESC-VCMs and their engineered tissues by selectively acting on sarc and mitoI(K, ATP).